Perilaku Konsumsi Tablet Besi berhubungan dengan Kadar Hb pada Ibu Hamil di Tegalampel Bondowoso - Dyah Ekowati (Universitas Islam Jember, 2018)
AbstractThe prevelance of anemia is still quite high in Indonesia there was 37.01%. East Java Province one of theprovince with high population of pregnant women with anemia 25.3%. One of districts of Bondowoso have a lotpregnant women with anemia was Tegalampel subdistrict with 55% (197 from 358 pregnant women). Thepercentage achieving the implementation of the program granting iron tablets in Bondowoso was high, but has notidentified pregnant women consuming iron tablets during pregnancy. This research have purpose to know therelation behavior of from tablet consumption with Hb level in pregnant women in Tegalampel Public Health Center.The research design used was the analytic with cross sectional. The population of research was the 2nd trimesterof pregnant women in the Tegalampel Public Health Center 103 pregnant women with purposive sampling wasobtained 82. Data was collcted by questionare and examination Hb level in pregnant women. Data have beencollected and analyced chi square to determine the relationship the consumption hebavior iron tablet with Hblevel. Based on the analysis of Chi Square test with 5% level of confidence (α=0.05) p value 0,001 obtained thereis relationship between behavior iron tablet consumption with Hb level in pregnant women in the TegalampelPublic Health Center.Key words: iron tablet, Hb level